Choosing and following a very low calorie diet program in Australia: A quasi‐mixed methods study to understand experiences, barriers, and facilitators in a self‐initiated environment. Issue 2 (6th December 2020) - Roesler, Anna; Marshall, Skye; Rahimi‐Ardabili, Hania; Duve, Emily; Abbott, Kylie; Blumfield, Michelle; Cassettari, Tim; Fayet‐Moore, Flavia
Abstract: Aim: In Australian adults, this study seeks to describe the experiences and factors associated with the perceived outcomes of using a very low calorie diet (VLCD) program for ≥4 weeks. Methods: A mixed method study using the method perspective was conducted to analyse individual semi‐structured interviews conducted via videoconference and cross‐sectional survey data. Australians 18 to 65 years were eligible if they were currently consuming at least one VLCD product daily for ≥4 weeks or had ceased consumption within 4 weeks. Interviews were thematically analysed. Results: Weight loss (19 kg [SD: 18 kg]) and duration (5 months [SD: 5 months]) of VLCD product use of the 31 participants (female: 97%, 44 [SD: 11] years, body mass index >30 kg/m 2 : 84%) were strongly correlated ( r = 0.73, P < .001). Participants' experiences were influenced by a journey of learning from their previous weight loss attempts, discerned the VLCD program as credible, and chose to commence the VLCD due to a convergence of internal motivators. Early health‐related outcomes were a reinforcing stimulus and participants developed new health behaviours but felt dependent on the VLCD long term. Throughout these experiences the participants identified various individual, program structure, and environment related factors which either facilitated their VLCD program use or created barriers to achieving their goals. Health care professionals were minimally engaged. Conclusions: A model of care to support facilitators and overcome barriers would mean more meaningful engagement of health care professionals to ultimately improve the experience and adherence of the VLCD program users in Australia.